2003
DOI: 10.1021/jp0362741
|View full text |Cite
|
Sign up to set email alerts
|

Density-Functional Theory Calculations of Aqueous Redox Potentials of Fourth-Period Transition Metals

Abstract: Aqueous M 3+ /M 2+ redox potentials for nine of the ten fourth-period transition metals, M, have been calculated with the use of DFT methodology in combination with the COSMO continuum model. Entropy contributions to the potentials are taken from experiments. The model introduces no adjustable parameters beyond those present in the underlying theoretical models. Inclusion of two solvation spheres (18 water molecules) is necessary. For the ions studied, the average absolute difference from experimental values i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
175
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(187 citation statements)
references
References 53 publications
10
175
2
Order By: Relevance
“…Interestingly, the predicted redox potentials for the negatively charged complexes (3−/4−) were significantly underestimated, which could be due to large solvation errors. Even the effect of explicit water molecules did not show any significant improvement for the computed redox potentials of the cationic complexes whereas significant improvement was observed for the anionic complexes, the latter one in agreement with an earlier study [79]. In addition, the QM/MM model approach was employed in which the thermodynamic integration method was used to predict the free energy of redox processes, and then the reduction potentials were predicted with respect to the SHE reference potential for TM complexes in aqueous solution.…”
Section: Transition Metal Complexessupporting
confidence: 91%
See 3 more Smart Citations
“…Interestingly, the predicted redox potentials for the negatively charged complexes (3−/4−) were significantly underestimated, which could be due to large solvation errors. Even the effect of explicit water molecules did not show any significant improvement for the computed redox potentials of the cationic complexes whereas significant improvement was observed for the anionic complexes, the latter one in agreement with an earlier study [79]. In addition, the QM/MM model approach was employed in which the thermodynamic integration method was used to predict the free energy of redox processes, and then the reduction potentials were predicted with respect to the SHE reference potential for TM complexes in aqueous solution.…”
Section: Transition Metal Complexessupporting
confidence: 91%
“…This explicit solvation (hydration) approach (six (first hydration) + twelve (second hydration) = eighteen water molecules) predicted the reduction potentials within a MUE of 0.29 eV of experimental redox potentials, a significant improvement by 1 eV over the previous approach. The local hydrogen bonding effects were important in order to obtain more accurate reduction potentials [79,130]. This confirms that the solvation process is usually an important aspect of the reduction potentials of TM complexes.…”
Section: Transition Metal Complexesmentioning
confidence: 52%
See 2 more Smart Citations
“…Owing to their importance, the development of first-principles techniques to study redox reactions has therefore been an area of considerable research interest. [1][2][3][4][5] In redox reactions, electrons are transferred from one species to another. Previous work 3,4 has shown that the standard local-density ͑LDA͒ and generalized gradient approximation ͑GGA͒ to density functional theory ͑DFT͒ lead to considerable errors in calculated redox energies.…”
Section: Introductionmentioning
confidence: 99%